Características clínicas y comorbilidades asociadas a lupus eritematoso sistémico en adultos, hospitalizados en el Hospital Regional de Loreto, en el período 2018 al 2023 - Valles Aguilar, Julio César (2025)
GENERAL OBJECTIVE: To determine the clinical characteristics and comorbidities associated with SLE in hospitalized adults at the Regional Hospital of Loreto in the period 2018 to 2023. MATERIALS AND METHODS: A quantitative, descriptive, analytical, cross sectional and retrospective study will be carried out. The study population will be all those medical records of patients with SLE over 18 years of age hospitalized in the medical service of the Regional Hospital of Loreto. Data will be analyzed using SPSS v25. CONCLUSIONS: Affected patients still present complications with severe organ damage, poor quality of life, and early mortality. Unlike other diseases in which the clinical manifestations are well defined, in the case of SLE, its clinical manifestations and comorbidities are characteristically heterogeneous.